1986
DOI: 10.1128/mcb.6.3.745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV light on small nuclear RNA synthesis: increased inhibition during postirradiation cell incubation.

Abstract: It has been shown previously that the synthesis of small nuclear RNAs (snRNAs) Ul, U2, U3, U4, and U5, in contrast to that of all other RNA species tested, decreases markedly within 2 h of cell incubation after exposure to UV light (254 nm), while pyrimidine dimers are being removed from DNA. We examined the possibility that the postirradiation cell incubation-dependent, UV light-induced inhibition of snRNA synthesis might reflect hypersensitivity of the snRNA transcriptional domains to single-stranded DNA nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…One initial hint of such an activity arose from studies demonstrating that the transcription of numerous snRNA genes by both RNA polymerase II and III is sharply down regulated in response to UV light treatment for an extended period beyond the time required for repair of lesions that might impair transcription [123][124][125][126][127][128]. This initial finding suggested that a factor activated in response to DNA damage was capable of restricting snRNA gene transcription or alternatively that an essential factor was lost after DNA damage.…”
Section: Human Snrna Gene Transcription In Response To Genomic Stressmentioning
confidence: 99%
“…One initial hint of such an activity arose from studies demonstrating that the transcription of numerous snRNA genes by both RNA polymerase II and III is sharply down regulated in response to UV light treatment for an extended period beyond the time required for repair of lesions that might impair transcription [123][124][125][126][127][128]. This initial finding suggested that a factor activated in response to DNA damage was capable of restricting snRNA gene transcription or alternatively that an essential factor was lost after DNA damage.…”
Section: Human Snrna Gene Transcription In Response To Genomic Stressmentioning
confidence: 99%
“…The differential metabolism of the U1-U6 UsnRNAs during the cellular proliferation, differentiation, development, and lung carcinogenesis has been reported [26][27][28][29][30][31]. The association of U5 in in vitro transformation [60] and reduced expression of UsnRNAs due to UV exposure have also been seen [61][62][63]. This indicates that, the alterations in the expression of U1B and U4-U6 UsnRNAs during EGCG induced apoptosis in S180 cells in vivo might have some effect on this phenomenon.…”
Section: Discussionmentioning
confidence: 84%
“…1A). 5s RNA transcription was monitored as a control, since it is not affected appreciably in whole cells at the W doses tested (Eliceiri, 1979;Eliceiri and Smith, 1983;Morra et al, 1986a). The U 1 gene fragment used, generated a -1.2-kb runoff transcript (ten times longer than 5 s RNA).…”
Section: Transcription Elongation In Vitromentioning
confidence: 99%
“…Second, snRNAs Ul-U5 are the only RNA species whose syntheses exhibit a delayed inhibition induced by UV light. It requires about 1-2 h r of cell incubation after irradiation and UV doses that are about tenfold lower than those needed to get comparable effects immediately after irradiation (the synthesis of messenger RNA, the major RNA polymerase 11 product, is not affected) (Eliceiri and Smith, 1983; Morra et al, 1986a). Several observations suggest that the immediate and delayed inhibitions of U1 RNA synthesis induced by UV radiation are separate reactions and that U1 RNA transcription is the step affected in both (Eliceiri and Smith, 1983; Morra et al, 1986a,b).…”
mentioning
confidence: 99%